Giant Photoinduced Chirality in Thin Film Ge2Sb2Te5. Issue 12 (14th October 2019) - Shanmugam, Janaki; Borisenko, Konstantin B.; Luers, Andrew; Ewart, Paul; Shah, Priyav; Williams, Benjamin A. O.; Craig, Christopher; Hewak, Daniel W.; Hussain, Rohanah; Jávorfi, Tamás; Siligardi, Giuliano; Bosman, Michel; et al.
Abstract : Induction, tuning, or amplification of chirality in various classes of materials and probing their chiral response are subjects of growing research. Herein, a large chiral signal that is rapidly imprinted in achiral amorphous Ge2 Sb2 Te5 (GST) thin films measured using synchrotron circular dichroism spectroscopy is reported. The chirality is induced by illuminating the films with pulsed circularly polarized (chiral) laser light for less than 2 μs in total. The effects of laser fluence and film thickness on the chiral response are described. The correlation of the optical results with structural studies by electron diffraction and model simulations suggests that alignment of reamorphized fragments in the crystallized film along the electric field vector of the light forms the centers that are responsible for the observed chirality. These results suggest opportunities for practical applications of this phenomenon and provide avenues for further studies of chirality induction in materials with impact in a wide range of disciplines. Abstract : A giant circular dichroism signal of different chirality can be rapidly imprinted in amorphous Ge2 Sb2 Te5 (GST) thin films by illuminating the films with pulsed circularly polarized (chiral) laser light. The large signal opens opportunities for practical applications of this phenomenon.